Effect of halogen substitution on the absorption and emission profile of organometallic perovskites - Ling, Jin Kiong; Rajan, Jose (EDP Sciences, 2017)
Comparative study on the optical properties of methylamide lead mono- and hybrid-halide perovskite samples, from the perspective of its crystal structure, which were synthesized in ambient condition (temperature ∼26.6 °C, humidity ∼65%), a step toward industrial commercialization, were carried out. In this study, in-depth information on both crystal structure and optical properties of the methylamide lead halide perovskite was the main focus, including study of relationship between these two factors via real world experimentation. Increment in lattice stain can be observed when the bromide or chloride ions were substituted, resulting in higher lattice strain in hybrid-halide samples. The lattice strain provides kinetic energy to the electrons, facilitating the promotion of exciton which increased the number of photon emitted during recombination. However, increasing lattice strain results in the widening of the energy gap of the samples by shifting the energy level to a higher or lower level. The results provide some insight on the relationship between crystal structure and optical properties of perovskite which paces a route for future cross-factor experimentation under uncontrolled ambient environment, in an effort to unravel more underlying working mechanism of perovskite solar cells.